Students' Reasoning Ability to Solve Problems in Statistical Materials With an Realistic Mathematics Education - Andriani Andriani; Wagino Wagino (Indo-MathEdu Intellectuals Journal, 2021)
Thinking is a series of mental processes of many kinds such as recalling things, fantasizing, memorizing, counting in the head, connecting some understanding, creating a concept or predicting various possibilities. Reasoning ability is a thought process that seeks to connect known facts or individuals to a conclusion. This research aims to find out students' reasoning ability in solving problems in statistical materials with a Realistic Mathematics Approach Class IX SMP Negeri 209 Jakarta. This type of research is qualitative descriptive with the number of subjects used, namely 1 person. The selected subjects are students who get the highest scores from the process of conducting tests carried out on 37 students. The instruments used are tests and interviews. Tests are used to select subjects and interviews are conducted to find out the student's reasoning ability in solving problems on the opportunity material. The data analysis technique used is to use qualitative data analysis, namely using the stage of data collection, data presentation and conclusion draw. Based on the results of data analysis conducted on subjects, peers, and subject teachers, it was obtained that the subject in learning and in the process of solving questions during the interview process used reasoning skills. In this study, the subject met the indicators of reasoning ability used in this study, namely the ability to submit conjectures, the ability to compile evidence, provide reasons for solving problems carried out, the ability to draw conclusions, and the ability to check the correctness of the answer.